MARKETING MANAJEMEN DAN DIVERSIFIKASI PRODUK PADA UMKM INDUSTRI KREATIF SOUVENIR - Ni Ketut Sari Adnyani; Komang Febrinayanti Dantes; Dewa Ayu Eka Agustini (Jurnal Pengabdian Kepada Masyarakat Media Ganesha, 2020)
This article aims to examine community service activities in helping SMEs Balinese Typical Souvenir Crafts in increasing sales through marketing management and product diversification. The benefit of the activity is to increase sales turnover so that it can expand marketing reach and increase income for souvenir craft business owners. The method of activity is carried out by means of discussion, focus group discussion (FGD) as a series of stages of coaching, empowerment and assistance through the provision of trainings, seminars, as well as assistance for the production and promotion of SMEs in the center of the creative souvenir industry. Product diversification is carried out by providing handicraft training with product design innovations. While the promotion strategy is carried out by helping respondents to actively use social media such as Instagram, Facebook, using the market place as a medium for online sales. The branding strategy is through brand design and placement on the packaging, which aims to introduce the respondent's brand. The result of this community service activity was an increase in production capacity up to 75%, an increase in the types and quality of souvenirs produced and an increase in sales turnover by 60%. This can be seen from the initial and final interview data that have been conducted by the community service implementation team. The conclusion of this activity is an increase in the production of both the types and quality of souvenirs produced, an increase in sales media and an increase in sales turnover and strengthen the existence of MSMEs in welcoming the new era of normality.